Changes in Macular Thickness after Phacoemulsification with Foldable Intraocular Lens with and without Post-Operative topical Non-Steroidal Anti-Inflammatory Drugs in Diabetes Mellitus - Muhammad Numan Qayyum, Ummaima Tahir, Danish Rafique, Abdul Rauf, Farhan Ali, Daniyal Yousaf (Pakistan Journal of Medical & Health Sciences, 2024)
Background: Diabetic patients undergoing phacoemulsification are at an increased risk of postoperative complications such as cystoid macular edema (CME). Postoperative inflammation contributes significantly to changes in central macular thickness (CMT). Topical non-steroidal anti-inflammatory drugs (NSAIDs) such as nepafenac have been proposed to reduce this risk, but evidence from the Pakistani population is limited. Objective: To compare changes in central macular thickness after phacoemulsification with foldable intraocular lens implantation in diabetic patients, with and without postoperative topical NSAIDs. Methods: This randomized controlled trial was conducted at the department of Ophthalmology, Sir Ganga Ram Hospital, Lahore, from January 2023 to June 2023. A total of 60 diabetic patients aged 40–80 years undergoing phacoemulsification were randomized equally into two groups: control (artificial tears) and NSAID (Nepafenac 0.1%). All patients received a standard steroid–antibiotic regimen. Central macular thickness (CMT) was measured using spectral-domain optical coherence tomography preoperatively and at 3 months postoperatively. Data were analyzed using SPSS version 26, with independent sample t-tests applied; p ≤ 0.05 was considered statistically significant. Results: Baseline demographic and clinical characteristics were comparable between the two groups (mean age 59.3 ± 8.1 years; male-to-female ratio 1.2:1). At 3 months, mean postoperative CMT was significantly higher in the control group (267.5 ± 61.2 µm) compared to the NSAID group (231.7 ± 21.5 µm; p = 0.011). Stratified analyses confirmed that the protective effect of nepafenac was consistent across age, gender, and diabetes duration subgroups. Conclusion: Topical nepafenac significantly reduced postoperative increases in macular thickness compared to control treatment in diabetic patients undergoing phacoemulsification. Incorporating NSAIDs into postoperative regimens may reduce the risk of CME and improve visual outcomes in this high-risk population. Keywords: Diabetes mellitus, Phacoemulsification, Nepafenac, Central macular thickness, Cataract surgery, Non-steroidal anti-inflammatory drugs.